Amorphous conjugated coordination polymer material and preparation method and application thereof

By directly synthesizing amorphous conjugated coordination polymers in the electrocatalytic nitrate reduction reaction, the problems of low catalytic efficiency and poor stability in the prior art are solved, high catalytic activity and stability are achieved, and the selectivity and yield of ammonia are improved.

CN119285977BActive Publication Date: 2025-04-11JIANGNAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411460085.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-04-11
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The existing electrocatalytic nitrate reduction reaction has the problems of high overpotential and low catalytic efficiency, and the loading rate of metal single-atom catalysts is low and the stability is poor.

Method used

The method of pre-coordinating first and then initiating polymerization is adopted to directly synthesize amorphous conjugated coordination polymers through water as a solvent to achieve high metal single atom loading rate and improve catalytic activity and stability.

Benefits of technology

High catalytic activity and stability are achieved, the overpotential of nitrate reduction reaction is reduced, and the selectivity and yield of ammonia are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285977B_ABST
    Figure CN119285977B_ABST
Patent Text Reader

Abstract

The present invention provides an amorphous conjugated coordination polymer material and a preparation method and application thereof, belonging to the technical field of new energy materials. The preparation method comprises the following steps: dissolving a metal salt and a conjugated organic ligand in water and mixing them evenly, pre-coordinating them first, then adding an initiator to polymerize them, and finally obtaining an amorphous conjugated coordination polymer material by centrifugation, washing and drying. The preparation process adopted by the present invention is environmentally friendly and is carried out in an aqueous system throughout the process; after the hydrothermal reaction, the unreacted metal salt and ligand or the residual initiator in the raw material can be removed by washing with water, and the product is easy to purify. Compared with the previous preparation methods, the present invention adopts a preparation method of pre-coordinating first and then initiating polymerization, and the obtained amorphous conjugated coordination polymer material can achieve a higher metal single atom loading rate. In addition, the amorphous conjugated coordination polymer material prepared by the present invention has good comprehensive performance and has extremely broad application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy materials, and in particular relates to an amorphous conjugated coordination polymer material and a preparation method and application thereof. Background Art

[0002] Ammonia is a core raw material in chemical fertilizers and modern chemical industry. It is a non-carbon energy carrier with an energy density of up to 4.3kWh kg -1 The autoignition point of ammonia can reach 651.1℃, and its safety is far superior to that of hydrogen. It can be used as an energy storage carrier and clean fuel. Using nitrate reduction reaction to convert nitrate into nitrogen or ammonia can promote the closure of the nitrogen cycle, and ammonia obviously has a higher added value. The Haber-Bosch process is currently the only synthetic method for large-scale production of ammonia, but the process consumes about 1% to 2% of the world's energy, accounts for 1.6% of the world's carbon dioxide emissions, and causes a lot of environmental pollution and energy consumption.

[0003] Electrocatalytic nitrate reduction reaction is a reasonable solution for producing ammonia using renewable electricity. It is a "green ammonia" synthesis process driven by clean energy at room temperature and pressure, using water as the hydrogen source. However, the nitrate reduction reaction is a reaction of eight electrons coupled to nine protons, with a complex reaction path and diverse products. It also has multiple problems such as high overpotential and low catalytic efficiency. Therefore, developing suitable catalysts to reduce the overpotential of nitrate reduction and improve the selectivity of ammonia is the key to improving the efficiency of power conversion and storage and ammonia yield.

[0004] Compared with traditional electrocatalysts, metal single-atom catalysts have unique structural characteristics and fully exposed active sites, and show significant performance improvements in various electrocatalytic reactions. However, due to the sharp increase in surface free energy, single atoms are prone to coupling and aggregation, affecting the stability of the catalyst. At the same time, the metal single atom loading rate is relatively low, generally less than 5%, and excessively strong metal-support interactions may reduce catalytic activity. Among them, conjugated coordination polymers, as a new type of single-atom catalyst, are very simple to synthesize. Through the design of conjugated organic ligands and metals, metal single atoms are highly dispersed and their stability is improved. In addition, the π-d electronic coupling between the d orbital of the metal ion and the π orbital of the conjugated organic ligand promotes the delocalization of its charge, which significantly improves the conductivity of the material.

[0005] In recent years, amorphous electrocatalysts have attracted extensive research attention due to their superior performance over crystalline catalysts under many conditions. The enhanced electrocatalytic activity of amorphous electrocatalysts is mainly attributed to the following factors: amorphous nanomaterials can achieve both surface- and volume-confined electrocatalysis, while crystalline nanomaterials can only perform surface catalysis. Amorphous electrocatalysts have richer defects, which is beneficial to improving the catalytic reaction rate. The flexibility of amorphous catalysts allows the active sites to adopt any geometry required for the electrocatalytic reaction and facilitates dynamic surface reconstruction, which can optimize the surface state. In addition, directly synthesized amorphous conjugated coordination polymer materials can be constructed from a wider range of metals and conjugated organic ligands than their crystalline and crystalline derivatives, and exhibit many unique material properties, such as higher electrochemical activity and stability. Summary of the invention

[0006] In view of the problems and shortcomings of the prior art, the present invention provides an amorphous conjugated coordination polymer material and a preparation method and application thereof. Using water as a solvent, an amorphous conjugated coordination polymer is directly synthesized by a pre-coordination and then initiation polymerization method, thereby achieving a high metal single atom loading rate and obtaining a material with high catalytic activity and high catalytic stability.

[0007] The first aspect of the present invention is to provide an amorphous conjugated coordination polymer material, wherein the amorphous conjugated coordination polymer material is a coordination polymer loaded with metal single atoms, and the amorphous conjugated coordination polymer material is in an amorphous state;

[0008] The metal single atoms include transition metal single atoms and / or main group metal single atoms, and the loading amount of the metal single atoms is not less than 20wt%;

[0009] The conjugated organic ligand includes any one or more of pyrrole, pyridine, pyrazole, imidazole, thiazole, pyrimidine and pyridazine.

[0010] In one embodiment, in the amorphous conjugated coordination polymer material, the loading amount of the metal single atom is 20wt%-25wt%.

[0011] The amorphous conjugated coordination polymer material obtained by the present invention has an amorphous structure and a high metal single atom loading rate; the metal single atoms are evenly dispersed in the amorphous conjugated coordination polymer material and can participate in the catalytic process more effectively. In addition, the long-range disorder and flexibility of the amorphous conjugated coordination polymer material can expose more metal active sites, which is conducive to enhancing the adsorption / diffusion of reactants and achieving improved catalytic activity and stability.

[0012] The second aspect of the present invention is to provide a method for preparing an amorphous conjugated coordination polymer material by pre-coordination followed by polymerization initiation, the method comprising the following steps:

[0013] S1. Dissolve the metal salt and the conjugated organic ligand in water to prepare a mixed solution, and preheat at 70-80° C. for pre-coordination;

[0014] S2, the mixed solution is reacted at 70-80° C. under stirring for 4-8 hours;

[0015] S3. After the reaction, the solid product is collected, washed and dried to obtain an amorphous conjugated coordination polymer material.

[0016] The present invention adopts a method of pre-coordination followed by polymerization initiation, and can directly prepare an amorphous conjugated coordination polymer material with short-range order and long-range disorder, which is conducive to rapid charge transfer. In addition, the preparation process does not use organic solvents and does not undergo high-temperature calcination treatment, which can retain the original structural characteristics of the conjugated coordination polymer material and effectively avoid structural damage to its metal single atom active sites.

[0017] In one embodiment, the metal salt is a soluble salt of a metal, and the soluble salt includes at least one of acetate, nitrate, and chloride.

[0018] Furthermore, in one embodiment, the metal includes at least one of a transition metal and / or a main group metal.

[0019] In one embodiment, the concentration of the metal salt in the mixed solution is 0.05 to 0.50 mol·L -1 , preferably 0.14 mol·L -1 .

[0020] In one embodiment, the concentration of the conjugated organic ligand in the mixed solution is 0.10 to 0.50 mol·L -1 , preferably 0.24 mol·L -1 .

[0021] In one implementation case, in step S2, the mixed solution is stirred after the initiator is added.

[0022] In one embodiment, the initiator includes an oxidizing initiator including a persulfate.

[0023] In one embodiment, the concentration of the initiator is 0.05 to 0.20 mol·L-1, preferably 0.14 mol·L -1 .

[0024] In one implementation case, in step S1, the preheating time is 15-60 minutes, preferably 30 minutes.

[0025] In one implementation case, in step S1, the preheating method is a water bath.

[0026] In one embodiment, the solution undergoes a color change during the reaction.

[0027] In one embodiment, the collected solid product is collected by centrifugation.

[0028] In one embodiment, the washing is performed by washing with water and ethanol in sequence.

[0029] In one implementation case, the drying is specifically normal pressure drying, the drying temperature is 50-80° C., preferably 60 minutes.

[0030] On the other hand, the present invention also provides an application of the above-mentioned amorphous conjugated coordination polymer material, including applications in the fields of electrocatalysis, electrochemical energy storage, sensing, or electronic devices.

[0031] In one embodiment, the electrocatalysis includes an amorphous conjugated coordination polymer material as a catalyst for nitrate reduction electrocatalytic reaction.

[0032] In one implementation case, in the nitrate reduction electrocatalytic reaction, an H-type electrolytic cell is used for the nitrate reduction electrocatalytic reaction, and the steps are as follows: a three-electrode system is used to formulate the amorphous conjugated coordination polymer material into a catalyst ink, which is coated on a hydrophobic carbon paper as a working electrode, a platinum mesh electrode as a counter electrode, a Hg / HgO electrode as a reference electrode, and a potassium hydroxide-potassium nitrate mixed solution as an electrolyte.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] 1. The preparation method of the amorphous conjugated coordination polymer material adopted in the present invention is simple and easy, does not use organic solvents, does not undergo high-temperature calcination treatment, is entirely water-based, and is green and environmentally friendly.

[0035] 2. Compared with the crystalline conjugated coordination polymer materials in the prior art, the amorphous conjugated coordination polymer materials prepared by the present invention have better performance and can obtain better electrocatalytic activity and stability.

[0036] 3. Compared with the amorphous conjugated coordination polymer material method in the prior art, the method of pre-coordination followed by polymerization of the present invention can prepare an amorphous conjugated coordination polymer material with a higher metal single atom content. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a schematic diagram of the synthesis and application of the cobalt-based amorphous conjugated coordination polymer material of Example 1.

[0038] Figure 2The structural characterization of the cobalt-based amorphous conjugated coordination polymer material of Example 1. Figure a is a scanning electron microscope photo, Figure b is an X-ray diffraction spectrum, Figure c is an X-ray photoelectron spectrum, and Figure d is an inductively coupled plasma mass spectrometry result.

[0039] Figure 3 This is a structural characterization of the copper-based amorphous conjugated coordination polymer material of Example 2. Figure a is a scanning electron microscope photo, Figure b is an X-ray diffraction spectrum, Figure c is an X-ray photoelectron spectrum, and Figure d is an inductively coupled plasma mass spectrometry result.

[0040] Figure 4 The structural characterization of the cobalt-based amorphous conjugated coordination polymer material of Example 3. Figure a is a scanning electron microscope photo, Figure b is an X-ray diffraction spectrum, Figure c is an X-ray photoelectron spectrum, and Figure d is an inductively coupled plasma mass spectrometry result.

[0041] Figure 5 The structural characterization of the cobalt-based amorphous conjugated coordination polymer material of Comparative Example 1 is shown in Figure a, Figure b is an X-ray diffraction spectrum, Figure c is an X-ray photoelectron spectrum, and Figure d is an inductively coupled plasma mass spectrometry result.

[0042] Figure 6 This is a linear sweep voltammetry curve of the cobalt-based amorphous conjugated coordination polymer material of Example 1.

[0043] Figure 7 The Faradaic efficiency and ammonia yield of the electrocatalytic nitrate reduction reaction of the amorphous conjugated coordination polymer material in Example 1.

[0044] Figure 8 This is the ammonia yield of the electrocatalytic nitrate reduction reaction of the amorphous conjugated coordination polymer material in Example 1 in nitrate solutions of different concentrations.

[0045] Fig. 9 This is the chronopotentiometry diagram of the amorphous conjugated coordination polymer material of Example 1. DETAILED DESCRIPTION

[0046] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] Unless otherwise specified, the sources of the reagents used in the embodiments of the present invention can be purchased from the market.

[0048] The present invention provides a characterization test result diagram of Example 1, and other embodiments all adopt the same characterization test method. Those skilled in the art can directly and unambiguously determine the content of the embodiments of the present invention through the characterization test method provided by the present invention.

[0049] like Figure 1 As shown, Example 1 provides a method for synthesizing a cobalt-based amorphous conjugated coordination polymer material. First, the cobalt salt and the conjugated organic ligand are preheated at a certain temperature to achieve pre-coordination between the metal and the conjugated organic ligand. Subsequently, an initiator is added to this pre-coordination system to carry out a polymerization reaction. Finally, a cobalt-based amorphous conjugated coordination polymer material sample is obtained by centrifugation, washing and drying. Specifically, the preparation method of the amorphous conjugated coordination polymer material of the present invention comprises the following steps: dissolving the metal salt and the conjugated organic ligand in water and mixing them uniformly, first performing pre-coordination, then adding the initiator for polymerization, and finally obtaining the amorphous conjugated coordination polymer material by centrifugation, washing and drying.

[0050] The process flow adopted by the present invention is environmentally friendly and is carried out in an aqueous system throughout the process; after the hydrothermal reaction, the unreacted metal salts and conjugated organic ligands or residual initiators in the raw materials can be removed by washing with water, and the product is easy to purify. Compared with the previous amorphous catalysts, the amorphous conjugated coordination polymer material obtained by the preparation method of pre-coordination followed by polymerization can achieve a higher metal single atom loading rate. In addition, the preparation process is simple and easy to operate, the process is environmentally friendly, and the prepared amorphous conjugated coordination polymer material has good comprehensive performance and has extremely broad application potential.

[0051] The present invention will be further described below in conjunction with specific embodiments. According to the following embodiments, the present invention can be better understood. However, it is easy for those skilled in the art to understand that the specific material ratios, process conditions and results described in the embodiments are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims.

[0052] Example 1: Preparation of a cobalt-based amorphous conjugated coordination polymer material

[0053] (1) Use a balance to weigh 6.97 g (0.028 mol) of cobalt acetate tetrahydrate and 3.27 g (0.048 mol) of pyrazole and dissolve them in 200 mL of water. Dissolve and mix them thoroughly, and heat them in a water bath for 30 minutes while stirring, keeping the temperature of the mixed solution at 80°C.

[0054] (2) Weigh 7.57 g (0.028 mol) of potassium persulfate and add it to the mixed solution obtained in step (1). Stir at 80° C. for 4 h. The color of the solution changes from pink to reddish brown.

[0055] (3) The reddish brown solution obtained in step (2) is centrifuged multiple times with water and ethanol in sequence, and the obtained solid is dried at 60° C. under normal pressure to obtain a cobalt-based amorphous conjugated coordination polymer material.

[0056] Example 2: Preparation of a copper-based amorphous conjugated coordination polymer material

[0057] (1) Use a balance to weigh 5.59 g (0.028 mol) of copper acetate monohydrate and 3.27 g (0.048 mol) of pyrazole and dissolve them in 200 mL of water. Dissolve and mix them thoroughly, and heat them in a water bath for 30 minutes while stirring, keeping the temperature of the mixed solution at 80°C.

[0058] (2) Weigh 7.57 g (0.028 mol) of potassium persulfate and add it to the mixed solution obtained in step (1). Stir at 80° C. for 5 h. The color of the solution changes from blue-green to brown-green.

[0059] (3) The brown-green solution obtained in step (2) is centrifuged multiple times with water and ethanol in sequence, and the obtained solid is dried at 60° C. under normal pressure to obtain a copper-based amorphous conjugated coordination polymer material.

[0060] Example 3: Preparation of a cobalt-based amorphous conjugated coordination polymer material

[0061] (1) Use a balance to weigh 3.49 g (0.014 mol) of cobalt acetate tetrahydrate and 1.61 g (0.024 mol) of pyrrole and dissolve them in 100 mL of water. Mix them thoroughly and heat them in a water bath for 30 minutes while stirring, keeping the temperature of the mixed solution at 80°C.

[0062] (2) The solution in step (1) was stirred at 80° C. for 6 h, and the color of the solution changed from pink to black.

[0063] (3) The black solution obtained in step (2) is centrifuged multiple times with water and ethanol in turn, and the obtained solid is dried at 60° C. under normal pressure to obtain a cobalt-based amorphous conjugated coordination polymer material.

[0064] Comparative Example 1: Preparation of a Cobalt-based Amorphous Conjugated Coordination Polymer Material

[0065] This comparative example is a method of preparing a cobalt-based amorphous conjugated coordination polymer material by polymerization first and then coordination, and is intended to study the effects of the coordination reaction and polymerization reaction on the material preparation.

[0066] (1) Use a balance to weigh 3.27 g (0.048 mol) of pyrazole and dissolve it in 200 mL of water. Dissolve it fully in a blue-mouth bottle and preheat for 30 min. Then add 7.57 g (0.028 mol) of potassium persulfate and heat in a water bath for 5 h while stirring. Keep the temperature of the mixed solution at 80°C.

[0067] (2) Weigh 6.97 g (0.028 mol) of cobalt acetate tetrahydrate and add it to the mixed solution obtained in step (1). Stir at 80° C. for 1 h. The color of the solution changes from yellow to pink.

[0068] (3) The pink solution obtained in step (2) is centrifuged multiple times with water and ethanol in turn, and the obtained solid is dried at 60° C. under normal pressure to obtain an amorphous conjugated coordination polymer material.

[0069] Test Example: Performance Test of Amorphous Conjugated Coordination Polymer Material Obtained in Example

[0070] Test Case 1: Structural Characterization

[0071] like Figure 2 This is a structural characterization of the cobalt-based amorphous conjugated coordination polymer material of Example 1. Figure a is a scanning electron microscope photo, from which it can be seen that Example 1 is uniformly distributed in granular form. Figure b is an X-ray diffraction spectrum, from which it can be seen that there are no obvious crystallization peaks, confirming its amorphous state; at the same time, there is no cobalt single substance peak. Figure c is an X-ray photoelectron energy spectrum, from which it can be seen that the cobalt-based amorphous conjugated coordination polymer material contains nitrogen and cobalt elements. From the figure, it can be seen that there is a Co-N bond, proving that Co-N is successfully coordinated. Figure d is the result of inductively coupled plasma mass spectrometry, the cobalt content is as high as 22.70%, and from Figure b it can be seen that there is no cobalt single substance, confirming that cobalt exists in the form of a single atom.

[0072] like Figure 3 This is a structural characterization of the copper-based amorphous conjugated coordination polymer material of Example 2. Figure a is a scanning electron microscope photo, from which it can be seen that Example 2 is evenly distributed in the form of flakes. Figure b is an X-ray diffraction spectrum, from which it can be seen that no obvious crystallization peaks appear, confirming its amorphous state; at the same time, there is no copper element peak. Figure c is an X-ray photoelectron energy spectrum, from which it can be seen that the copper-based amorphous conjugated coordination polymer material contains nitrogen and copper elements. From the figure, it can be seen that there is a Cu-N bond, proving that Cu-N is successfully coordinated. Figure d is the result of inductively coupled plasma mass spectrometry, the copper content is as high as 21.96%, and from Figure b it can be seen that there is no copper element, confirming that copper exists in the form of single atoms.

[0073] like Figure 4This is a structural characterization of the cobalt-based amorphous conjugated coordination polymer material of Example 3. Figure a is a scanning electron microscope photo, from which it can be seen that Example 3 is uniformly distributed in granular form. Figure b is an X-ray diffraction spectrum, from which it can be seen that there are no obvious crystallization peaks, confirming its amorphous state; at the same time, there is no cobalt single substance peak. Figure c is an X-ray photoelectron energy spectrum, from which it can be seen that the cobalt-based amorphous conjugated coordination polymer material contains nitrogen and cobalt elements. From the figure, it can be seen that there is a Co-N bond, proving that Co-N is successfully coordinated. Figure d is the result of inductively coupled plasma mass spectrometry, the cobalt content is as high as 24.70%, and from Figure b it can be seen that there is no cobalt single substance, confirming that cobalt exists in the form of a single atom.

[0074] like Figure 5 This is a structural characterization of the cobalt-based amorphous conjugated coordination polymer material of comparative example 1. Figure a is a scanning electron microscope photo, from which it can be seen that comparative example 1 is uniformly distributed in a spherical shape. Figure b is an X-ray diffraction spectrum, from which it can be seen that no obvious crystallization peaks appear, confirming its amorphous state; at the same time, there is no cobalt single substance peak. Figure c is an X-ray photoelectron energy spectrum, from which it can be seen that the cobalt-based amorphous conjugated coordination polymer material contains nitrogen and cobalt elements. From the figure, it can be seen that there is a Co-N bond, proving that Co-N is successfully coordinated. Figure d is the result of inductively coupled plasma mass spectrometry, and the cobalt content is only 1.88%. Combining the results of X-ray diffraction and inductively coupled plasma mass spectrometry, it can be seen that there is no cobalt single substance in the cobalt-based amorphous conjugated coordination polymer material of comparative example 1, confirming that the cobalt component exists in the form of a single atom.

[0075] Through the comparative test of Example 1 and Comparative Example 1, it can be seen that the cobalt metal single atom content of the cobalt-based amorphous conjugated coordination polymer material obtained by the method of preparing by pre-coordination first and then initiating polymerization in Example 1 is much higher than that of the cobalt-based amorphous conjugated coordination polymer material obtained by the method of preparing by first initiating polymerization and then coordination in Comparative Example 1. This indicates that the method of pre-coordination first and then initiating polymerization of the present invention can significantly improve the metal loading rate.

[0076] Test Example 2: Characterization of Catalytic Reduction Performance

[0077] The cobalt-based amorphous conjugated coordination polymer material prepared in Example 1 is used in the electrocatalytic reaction of nitrate reduction, and the nitrate reduction electrocatalytic reaction is carried out using an H-type electrolytic cell, and the steps are as follows: a three-electrode system is used to prepare the amorphous conjugated coordination polymer material into a catalyst ink, which is coated on a hydrophobic carbon paper as a working electrode, a platinum mesh electrode as a counter electrode, a Hg / HgO electrode as a reference electrode, and a potassium hydroxide-potassium nitrate mixed solution as an electrolyte.

[0078] like Figure 6 The linear sweep voltammetry curve of the cobalt-based amorphous conjugated coordination polymer material of Example 1 is shown. It can be seen from the figure that the prepared cobalt-based amorphous conjugated coordination polymer material has a high conductivity in the presence of 0.5M KNO3 The electrochemical nitrate reduction performance was excellent in 1 M KOH aqueous solution, reaching 100 mA cm at -0.4 V reversible hydrogen electrode (RHE). -2 Especially at -1.1V (vs.RHE), the current density reaches -798.3mA cm -2 .

[0079] like Figure 7 The electrochemical test results of the cobalt-based amorphous conjugated coordination polymer material of Example 1 are shown. It can be seen that the material has excellent nitrate reduction performance. Specifically, the maximum Faraday efficiency of Example 1 is 99.6%, and the ammonia yield is 1.83 mmol h -1 mg -1 In addition, at -1.3 V (vs. RHE), the ammonia yield of Example 1 can reach up to 12.11 mmol mg - 1 h -1 , while maintaining a high Faraday efficiency of 88.9%. The electrochemical test method is as follows: 3 The electrocatalytic nitrate reduction performance of the prepared catalyst was tested in 1M KOH aqueous solution.

[0080] like Figure 8 The yield of the electrocatalytic nitrate reduction reaction of the amorphous conjugated coordination polymer material in Example 1 in nitrate solutions with different concentrations. Specifically, at low concentrations of NO 3 - The ammonia yields of Example 1 in 10 and 50 mM electrolytes were 0.48 and 1.59 mmol h, respectively. -1 mg -1 .

[0081] like Fig. 9 The chronopotentiometry of the cobalt-based amorphous conjugated coordination polymer material of Example 1 is shown. It can be seen from the figure that the prepared cobalt-based amorphous conjugated coordination polymer material exhibits good electrochemical stability at -1.1V (vs. RHE). Specifically, in a solution containing 0.5M KNO 3 It ran stably in 1M KOH solution for 220 h, and there was no obvious decay in its current density or Faradaic efficiency. The Faradaic efficiency was stabilized at around 98%, and its ammonia production accumulation continued to increase.

[0082] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. An amorphous conjugated coordination polymer material, characterized in that: The amorphous conjugated coordination polymer material is a ligand loaded with metal single atoms, the amorphous conjugated coordination polymer material is in an amorphous state, and the metal single atoms are uniformly dispersed in the amorphous conjugated coordination polymer material; The metal single atoms include transition metal single atoms and / or main group metal single atoms, and the loading amount of the metal single atoms is not less than 20 wt%; The ligand includes at least one of pyrrole, pyridine, pyrazole, imidazole, thiazole, pyrimidine, and pyridazine; The method for preparing the amorphous conjugated coordination polymer material comprises the following steps: S1. Dissolve the metal salt and the conjugated organic ligand in water to prepare a mixed solution, and preheat at 70-80 °C for pre-coordination; S2, adding an initiator to the mixed solution, and stirring at 70-80 ° C for 4-8 h; S3. After the reaction, the solid product is collected, washed and dried to obtain an amorphous conjugated coordination polymer material.

2. The amorphous conjugated coordination polymer material according to claim 1, characterized in that: In the amorphous conjugated coordination polymer material, the loading amount of the metal single atom is 20 wt%-25 wt%.

3. The amorphous conjugated coordination polymer material according to claim 1, characterized in that: The metal salt is a soluble salt of a metal, and the soluble salt includes at least one of acetate, nitrate, and chloride. The metal includes at least one of a transition metal and / or a main group metal.

4. The amorphous conjugated coordination polymer material according to claim 1, characterized in that: The concentration of the metal salt in the mixed solution is 0.05-0.50 mol·L -1 .

5. The amorphous conjugated coordination polymer material according to claim 4, characterized in that: The concentration of the metal salt in the mixed solution is 0.14 mol·L -1 .

6. The amorphous conjugated coordination polymer material according to claim 1, characterized in that: The concentration of the conjugated organic ligand in the mixed solution is 0.10-0.50 mol·L -1 .

7. The amorphous conjugated coordination polymer material according to claim 6, characterized in that: The concentration of the conjugated organic ligand in the mixed solution is 0.24 mol·L -1 .

8. The amorphous conjugated coordination polymer material according to claim 1, characterized in that: In step S2, the initiator includes an oxidizing initiator including persulfate.

9. The amorphous conjugated coordination polymer material according to claim 1, characterized in that: In step S2, the concentration of the initiator in the reaction system is 0.05-0.20 mol·L -1 .

10. The amorphous conjugated coordination polymer material according to claim 9, characterized in that: The concentration of the initiator in the reaction system was 0.14 mol·L -1 .

11. The amorphous conjugated coordination polymer material according to claim 1, characterized in that: In step S1, the preheating time is 15-60 min.

12. The amorphous conjugated coordination polymer material according to claim 11, characterized in that: In step S1, the preheating time is 30 min.

13. The amorphous conjugated coordination polymer material according to claim 1, characterized in that: In step S3, the solid product is collected by centrifugation.

14. The amorphous conjugated coordination polymer material according to claim 1, characterized in that: In step S3, the washing is specifically washing with water and ethanol in sequence.

15. The amorphous conjugated coordination polymer material according to claim 1, characterized in that: In step S3, the drying is specifically normal pressure drying, and the drying temperature is 50-80 ° C.

16. Use of the amorphous conjugated coordination polymer material according to any one of claims 1 to 15, characterized in that: This includes applications in electrocatalysis or electrochemical energy storage or sensing or electronic devices.

17. The use according to claim 16, characterized in that The electrocatalysis comprises an amorphous conjugated coordination polymer material as a catalyst for nitrate reduction electrocatalysis reaction.

Citation Information

Patent Citations

  • Conjugated conductive polymer modified copper-based catalyst as well as preparation method and application thereof

    CN114277402A

  • Conjugated polymer loaded metal platinum nano-particles, preparation method thereof and application of conjugated polymer loaded metal platinum nano-particles in photocatalytic hydrogen evolution

    CN114405544A